SIGNIFICANCE OF LITERATURE IN EVOLUTION OF ENVIRONMENT - Dr. Sandeep Kumar, Dr Abha Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The environment is the collection of the socioeconomic, biological or chemical factors that make up the surroundings of a human. It comprises both living and non-living beings that exist in agreement with one another. In representing our environment, literature plays a critical role and is the reflection of modern-day society. ’Eco-criticism’ is the term for the association among literature and the environment. Basically, it is the analysis of depictions of life and the connection among literature as well as the environment. There is also a strong connection between literature and nature that most authors have wonderfully portrayed. In today’s scenario, environmentalism, eco-criticism and ecology have become relevant concepts. Nature seems to have been a real concern in several literatures and globalization has been the dominant force in environmental destruction.